2010
DOI: 10.1007/s12185-010-0658-x
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of IgE-multiple myeloma presenting with systemic amyloidosis 2 years after cervical plasmacytoma resection

Abstract: A 69-year-old man suffered from a fractured cervical vertebra, and magnetic resonance imaging revealed a solitary mass occupying the injured lesion. Surgical resection of the mass was conducted, and the infiltration of plasma cells expressing IgE-lambda monoclonal protein was shown on pathological investigation. Concurrently, a monoclonal band of IgE-lambda was shown in the sera on immunoelectrophoresis, and the proliferation of plasma cells (more than 10%) was also detected in bone marrow aspirates. A rare Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…A case of prolonged survival, on the other hand, has been documented as well [4]. Other rare clinical presentations included cutaneous manifestation, systemic amyloidosis, and elevated serum CA125 [8][9][10]. Our patient's clinical presentation also included lytic bone lesions and clinical evidence of involvement of the mesentery and lymph nodes, but she also presented with an orbital mass, which differed from what has been previously reported.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…A case of prolonged survival, on the other hand, has been documented as well [4]. Other rare clinical presentations included cutaneous manifestation, systemic amyloidosis, and elevated serum CA125 [8][9][10]. Our patient's clinical presentation also included lytic bone lesions and clinical evidence of involvement of the mesentery and lymph nodes, but she also presented with an orbital mass, which differed from what has been previously reported.…”
Section: Discussionsupporting
confidence: 42%
“…Since the first case of IgE PCM reported in 1967 [2], there have been only 47 cases of IgE PCM described in the English literature [2][3][4][5][6][7][8][9][10]. Aside from the typical clinical presentations of PCM, rare cases of IgE PCM involving the skin, breast, and orbit have also been reported [8,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with melphalan-prednisone and bortezomib is of limited value in most patients with LCCD liver involvement (24,25). Moreover Samanez et al reported a liver failure with rapid fatal outcome that debuted after the first cycle of VAD (26).…”
Section: Discussionmentioning
confidence: 99%
“…IgA was found in 34 % cases (15 cases) including one case of biclonal expression with IgD [16]. Three cases of clonal IgD [14,20], two cases of monoclonal light chain production [21,22], one case of clonal IgE production [23], and one nonsecretory myeloma was reported.…”
Section: Discussionmentioning
confidence: 99%